MEETING OF EXPERTS ON THE DEVELOPMENT OF THE "INSUFFICIENCY OF VITAMIN D IN CHILDREN AND ADOLESCENTS OF THE RUSSIAN FEDERATION: MODERN APPROACHES TO CORRECTION" NATIONAL PROGRAM - Editorial article ("Paediatrician" Publishers LLC, 2016)
.